Bank regulatory reforms in Africa - Murinde, Victor (Palgrave Macmillan studies in banking and financial institutions, 2012)
In the wake of the recent financial crisis that has created enormous regulatory risks, changes in the content of banking regulation are crucial. In this book, policy makers and advisors from central banks across Africa discuss this topical subject, focussing on how to enhance bank competition and intermediation efficiency in the region